Retrobulbar blood flow and visual field alterations after acute ethanol ingestion - Weber A (Dove Medical Press, 2013)
Anke Weber, Andreas Remky, Marion Bienert, Klaudia Huber-van der Velden, Thomas Kirschkamp, Corinna Rennings, Gernot Roessler, Niklas Plange Department of Ophthalmology, RWTH Aachen University, Aachen, Germany Background: The purpose of this study was to test the effect of ethyl alcohol on the koniocellular and magnocellular pathway of visual function and to investigate the relationship between such visual field changes and retrobulbar blood flow in healthy subjects. Methods: In 12 healthy subjects (mean age 32 ± 4 years), color Doppler imaging, short-wavelength automated perimetry, and frequency doubling perimetry was performed before and 60 minutes after oral intake of 80 mL of 40 vol% ethanol. Mean and pattern standard deviations for short-wavelength automated and frequency doubling perimetry were assessed. End diastolic velocity (EDV) and peak systolic velocity (PSV) were measured in the central retinal and ophthalmic arteries using color Doppler imaging. Systemic blood pressure, heart rate, intraocular pressure, and blood alcohol concentration were determined. Results: Mean PSV and EDV in the central retinal artery showed a significant increase after alcohol intake (P = 0.03 and P = 0.02, respectively). Similarly, we found a significant acceleration of blood flow velocity in the ophthalmic artery (P = 0.02 for PSV; P = 0.04 for EDV). Mean intraocular pressure decreased by 1.0 mmHg after alcohol ingestion (P = 0.01). Retinal sensitivity in short-wavelength automated perimetry did not alter, whereas in frequency doubling perimetry, the mean deviation decreased significantly. Systolic and diastolic blood pressure did not change significantly. Mean blood alcohol concentration was 0.38 ± 0.16 g/L. Conclusion: Although ethanol is known to cause peripheral vasodilation, our subjects had no significant drop in systemic blood pressure. However, a significant increase of blood flow velocity was seen in the retrobulbar vessels. Regarding visual function, moderate alcohol consumption led to reduced performance in the magnocellular visual system tested by frequency doubling perimetry, but had no effect on short-wavelength automated perimetry. Keywords: visual field, retrobulbar blood flow, frequency doubling perimetry, short-wavelength automated perimetry